Flow Injection–Indirect Spectrophotometry for Hydroquinone Analysis Based on the Formation of Iron(II)-Phenanthroline Complex - Mariam Mohamed Omar Alshibani; Hermin Sulistyarti; Akhmad Sabarudin (Chemistry Department, The University of Brawijaya, 2019)
Hydroquinone is an organic antioxidant widely used for skin lightening products which can cause negative impact in excessive use. This study is focused on the development of fast method for the determination of hydroquinone using flow injection-indirect spectrophotometry based on the formation of red complex Iron(II)-phenanthroline. In this method, hydroquinone reduced iron(III) to iron(II) which in the presence of phenanthroline formed Iron(II)-phenanthroline complex detected at maximum wavelength of 510 nm. The common operational and chemical conditions were optimized and the effect of several interfering compounds was also studied to achieve the highest sensitivity with acceptable analysis time. The optimum method performance was obtained under the conditions of 100 µL sample volume, 50 cm mixing coil-1and 75 cm mixing coil-2, 5 ml/min flow rate, 100 mgL-1 Iron(III) concentration, and 0.15 % phenanthroline. Under these conditions the proposed FI-spectrophotometry gave results to linear calibration over the concentration range from 2-100 mgL-1 (y = 0.028x and R2 of 0.999). The method was not interfered in the presence of vitamin C 1 mgL-1 and resorcinol up to 10 mgL-1. However, the higher concentration of vitamin C ³10 ppm and resorcinol ³ 20 ppm gave significant error of measurements. Method validation using standard additions gave results to average recovery value of 97.02 %, which indicates that the FI-spectrophotometry method can be used as an alternative method for determining hydroquinone in cosmetic. Key words: Hydroquinone, flow injection, spectrophotometry, iron, phenanthroline.